A new species of Margotrema (Digenea, Allocreadiidae) from the leopard splitfin Xenotaenia resolanae (Cyprinodontiformes, Goodeidae) from west-central Mexico - de León, Gerardo Pérez-Ponce; Martínez-Aquino, Andrés; Mendoza-Garfias, Berenit (Zootaxa, 2013)
A new species of Margotrema is herein described from the intestine of the freshwater fish Xenotaenia resolanae from the Cuzalapa River, Jalisco State, on the Pacific slope of west-central Mexico. The new species was first recognized after a molecular phylogenetic analysis which explored the genetic variation at the intraspecific level of Margotrema spp across central Mexico. Sequences of mitochondrial (COI) and nuclear (ITS1) genes were obtained for 125 individuals, and a general mixed Yule-coalescent analysis (GMYC) for species delimitation of both genes allowed the recognition of an independent evolutionary lineage, representing an undescribed species of Margotrema. Detailed morphological observations allowed the species description. The new species is easily distinguished from the other valid species of the genus, M. bravoae, by having vitelline follicles restricted to the region between the pharynx and the ventral sucker a wider and more prominent ventral sucker, larger eggs, and symmetrical testes.